Hemorrhagic stroke as a serious complication of scorpion sting: Systematic review with an exemplary case description - Turgut, Yaşar Barış; Cakir, Tumay (Nepal Journal of Neuroscience, 2024)
Introduction: Scorpion stings are toxicological emergencies with serious central nervous system complications including intracranial hemorrhage (ICH). The aim of this study is to review the reported cases of ICH as a complication of scorpion sting, with a description of an exemplary case of subarachnoid hemorrhage. Material and Methods: A systematic search was performed according to Preferred Reporting Items for Systematic Review and Meta-Analyses (PRISMA) guidelines. Data regarding demographics, clinical presentation, causative species of the scorpion, treatments, and outcomes were collected. Results: Fifteen reports documenting 16 cases were included in our review, evaluating demographical features and outcomes of the cases of ICH from scorpion stings. Reported cases were from tropical and subtropical regions, primarily from India followed by Turkey and most frequently in young adult male individuals. Of the 8 reported cases with sufficient information for analysis, 4 were by M. tamulus, while N. Hierochonticus, L. Quinquestriatus, P. swannerdani and T. Trivitatus each described 1 case. Out of 14 cases with follow-up information, there were 12 cases with ICH involving the basal nuclei or cerebral lobes and subarachnoid hemorrhage occured in only 2 cases; all cases except one were treated conservatively and their outcomes included 7 with complete recovery, 2 were ambulatory, and 5 died. Conclusion: Hemorrhagic stroke from scorpion sting poisoning is a life-threatening emergency where early diagnosis and prompt management are vital for recovery.